Improving in-plane and out-of-plane thermal conductivity of polyimide/boron nitride film with reduced graphene oxide by a moving magnetic field induction. (22nd March 2022) - Liu, Dongxu; Chi, Hongtao; Ma, Chuanguo; Song, Muyuan; Zhang, Ping; Dai, Peibang
Abstract: To develop high-performance thermal management materials, herein, the hybrid nanoparticle (GF) of reduced graphene oxide and magnetic needle-like ferro oxide was successfully prepared by in-situ modification of polydopamine. A moving magnetic field induction (MF) strategy with a potential of large-scale application was proposed to realize the alignment of the GF in the boron nitride (BN)/polyimide composite film. The GF nanoparticles were partially aligned at a certain angle from in-plane direction of the composite film and synergistically improved the thermal conductivity network with the BN, which results in simultaneous enhancement in the in-plane and out-of-plane thermal conductivity. At 30 wt% filler content, the in-plane and out-of-plane thermal conductivity of the composite film reached 2.532 W m −1  K −1 and 0.425 W m −1  K −1, which is 1233% and 150% higher than that of the pure PI, respectively. This work developed a novel and efficient approach for the design of high thermal conductive materials. Graphical abstract: Image 1 Highlights: 1. Reduced graphene/ferro oxide hybrid nanoparticle (GF) was prepared by PDA modification. 2. A moving magnetic field induction (MF) was carried out to prepare GF-BN/PI film efficiently. 3. In-plane and out-of-plane thermal conduction of the film are enhanced simultaneously by MF.